2022
DOI: 10.1113/jp283345
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic interplay of PIP2 and ATP in the regulation of the KATP channel

Abstract: ATP-sensitive potassium (KATP) channels couple the intracellular ATP concentration to insulin secretion. KATP channel activity is inhibited by ATP binding to the Kir6.2 tetramer and activated by phosphatidylinositol-4,5-bisphosphate (PIP2). Here, we use molecular dynamics (MD) simulation, electrophysiology and fluorescence spectroscopy to show that ATP and PIP2 occupy different binding pockets that share a single amino acid residue, K39. When both ligands are present, K39 shows a greater preference to co-ordin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…The finding that some mutations reduce channel response to both ligands led to a hypothesis that these mutated residues may be involved in the binding of both ligands. Recently, molecular dynamics studies found that Kir6.2 residues R54 and K39 interact with both ATP and PIP 2 ( Pipatpolkai et al, 2022 ; Sung et al, 2022 ). Mutation of both R54 and K39 to alanine has been shown to reduce ATP as well as PIP 2 sensitivities ( Cukras et al, 2002 ).…”
Section: Structural Insights On K Atp Channel Regu...mentioning
confidence: 99%
“…The finding that some mutations reduce channel response to both ligands led to a hypothesis that these mutated residues may be involved in the binding of both ligands. Recently, molecular dynamics studies found that Kir6.2 residues R54 and K39 interact with both ATP and PIP 2 ( Pipatpolkai et al, 2022 ; Sung et al, 2022 ). Mutation of both R54 and K39 to alanine has been shown to reduce ATP as well as PIP 2 sensitivities ( Cukras et al, 2002 ).…”
Section: Structural Insights On K Atp Channel Regu...mentioning
confidence: 99%
“…(18) This combined with the recent in silico evidence suggesting PS may compete for the PIP2-binding site led us to investigate the PIP2-PS-Kir2.1 signaling axis in resistance arteries. There is also evidence indicating other vascular potassium channels, including SK and KATP, are regulated by PIP2 (61,62), and these channels may be affected in our vasodilation studies where exogenous lipids are added to intact arteries. However, our accumulation of evidence obtained from diverse experimental approaches gives us confidence in concluding that PS inhibits Kir2.1-mediated vasodilation through an interaction at the MEJ.…”
Section: Phosphatidylserine Regulation Of Kir21mentioning
confidence: 77%
“…2b, 5c). Previous molecular dynamics simulations, using ATP-bound closed structures of Kir6.2 tetramer 51 or tetramer of Kir6.2 plus SUR1-TMD0 38 with a single PIP 2 molecule docked in the conserved PIP 2 binding site, found that Kir6.2-K39 51 or both K39 and R54 38 switched between ATP binding and PIP 2 binding. In the SUR1/Kir6.2 Q52R open structure, we see Kir6.2-K39, rather than binding PIP 2 in the conserved site, binds the second PIP 2 in the novel site.…”
Section: Discussionmentioning
confidence: 99%